Sarcopenia is associated with the risk of significant liver fibrosis in metabolically unhealthy subjects with chronic hepatitis B. Issue 3 (19th June 2018) - Han, E.; Lee, Y.‐h.; Kim, B. K.; Park, J. Y.; Kim, D. Y.; Ahn, S. H.; Lee, B.‐W.; Kang, E. S.; Cha, B.‐S.; Han, K.‐H.; Kim, S. U.
Summary: Background: Sarcopenia is significantly associated with the degree of liver fibrosis. This study investigated the influence of sarcopenia on liver fibrosis in individuals with chronic hepatitis B. Methods: Data from the Korean National Health and Nutrition Examination Surveys 2008‐2011 were analysed. The sarcopenia index (total appendicular skeletal muscle mass [kg]/body mass index [kg/m 2 ]) was calculated using dual‐energy X‐ray absorptiometry. Sarcopenia was defined as the lowest quintile sarcopenia index value (cut‐offs: 0.89 for men and 0.58 for women). The fibrotic burden was assessed using the nonalcoholic fatty liver disease fibrosis score and fibrosis‐4 index. Significant fibrosis was defined as the highest nonalcoholic fatty liver disease fibrosis score quartile and a fibrosis‐4 index ≥2.67. Results: Among the 506 respondents with chronic hepatitis B (258 men and 248 women), the nonalcoholic fatty liver disease fibrosis score and fibrosis‐4 index identified sarcopenia and significant fibrosis in 126 (24.9%) and 217 (42.9%), respectively. Sarcopenia was significantly associated with significant fibrosis, regardless of the fibrosis prediction model used (all P < 0.05). When the study population was stratified according to metabolic factors, sarcopenia was specifically associated with an increased risk of significant fibrosis among subgroups with obesity, insulin resistance, metabolic syndrome and liver steatosis (odds ratio 2.37‐3.57; all P < 0.05). An independent association between sarcopenia and significant fibrosis was identified after adjusting for other confounders (odds ratio 2.67‐3.62 by the nonalcoholic fatty liver disease fibrosis score and 2.04‐2.62 by the fibrosis‐4 index; all P < 0.05). Conclusions: Sarcopenia is associated with significant fibrosis in subjects with chronic hepatitis B, specifically those with obesity, insulin resistance, metabolic syndrome and liver steatosis. Abstract : Linked Content This article is linked to Mudaliar and Liu paper. To view this article visit https://doi.org/10.1111/apt.14894 .